2021
DOI: 10.1007/s12132-021-09441-9
|View full text |Cite
|
Sign up to set email alerts
|

Urban Climate Change Governance within Centralised Governments: a Case Study of Giza, Egypt

Abstract: Urban climate governance on the subnational and local government levels requires multilevel governance and local autonomy. Within centralised governments, climate action becomes challenging. Moreover, in developing countries, development needs are usually prioritised, while climate action is viewed as an unaffordable luxury. In a centralised, middle-income country like Egypt, climate action is a challenge for all government levels. This research investigates the current state and the prospect of urban climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Regarding impact and vulnerability, there are several reports that indicate that higher officials as well as the community well understood vulnerable places. Climate-change governance in cities require access to current, contextspecific sources of data, including future climate predictions, GHG inventories results, climate vulnerability assessments, and impacts, such as heat waves and floods [27,34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding impact and vulnerability, there are several reports that indicate that higher officials as well as the community well understood vulnerable places. Climate-change governance in cities require access to current, contextspecific sources of data, including future climate predictions, GHG inventories results, climate vulnerability assessments, and impacts, such as heat waves and floods [27,34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that a shortage of finance is another factor for the implementation of climate-change response measures [27,29,[32][33][34]. Mostly, local governments or municipal authorities face a shortage of finance to implement mitigation and adaptation because of the existence of many competing issues on urban agendas [27,32,35].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations